Comparing Chinese and Western classroom learning environment research: a bibliometric analysis and visualization - Cai, Juan; Backer, Free De; Vandermeersche, Geert; Lombaerts, Koen (Frontiers in Psychology, 2023)
A comprehensive cross-national understanding of the classroom learning environment (CLE) is critical to advancing CLE’s development. This study compares the English and Chinese CLE literature to enhance a complete understanding of CLE. We conducted bibliometric analysis on 3130 English literature from Social Sciences Citation Index (SSCI) and 1261 Chinese literature from the Chinese Social Sciences Citation Index (CSSCI). The results show that both Chinese and English literature focus on the influence of CLE on students' cognitive and affective learning outcomes and the incorporation of information technology in CLE. The results also reveal the differences between Chinese and English literature from two perspectives: 1) Chinese CLE research mainly focuses on English education, and English CLE research mainly focuses on science education. 2) Chinese CLE research mainly analyzed the pedagogical aspect of CLE, while English CLE research focused on CLE's social and psychological aspects. We also discussed that future research should focus on 1) the balance of analyzing CLE from the perspective of students and other educational stakeholders such as teachers and school leaders, 2) student differences from the pedagogical level, 3) the physical level of CLE, 4) the use of statistical methods such as structural equation modeling that can analyze the mechanisms underlying the effects of CLE on student learning and 5) the interdisciplinary research on CLE.